UJI EFEKTIVITAS BIO-ORGANIC FERTILIZER (PUPUK ORGANIK HAYATI) DALAM MENSUBSTITUSI KEBUTUHAN PUPUK ANORGANIK PADA TANAMAN SWEET SORGHUM [SORGHUM BICOLOR (L.) MOENCH] - Ester LN Lumbantobing; Fahrizal Hazra; Iswandi Anas (Jurnal Ilmu Tanah dan Lingkungan, 2008)
The aim of research was to examine the effectiveness of bio-organic fertilizer to substitute inorganic fertilizer necessity on sweet sorghum [Sorghum bicolor (L.) Moench] vegetative growth. This research was carried out in the University Farm green house Cikabayan and in the Leuwikopo Experiment Field, Institut Pertanian Bogor. The green house experiment used completely randomized design with six treatments, namely: 1. No fertilizer (control), 2. 100%NPK, 3. 50%N + DOP, 4. 50%NPK + Fertismart, 5. 50%NPK + Ponti, dan 6. 50%NPK + Biost. The field experiment used completely randomizes block design with seven treatments, namely: 1. No fertilizer (control), 2. 50%NPK, 3. 100%NPK, 4. 50%N + DOP, 5. 50%NPK + Fertismart, 6. 50%NPK + Ponti, and 7. 50%NPK + Biost. Materials which was used were super sugar variety, NPK fertilizers, bio-organic fertilizer Fertismart, Ponti, Biost, and organic fertilizer Double Organic Phosphate (DOP).The results of greeen house research showed that bio-organic fertilizer could increase crop height, number of leaves, wet weight upper crop, dry weight upper crop, wet weight root, and dry weight root of sweet sorghum than control and same with treatment of 100%NPK. Treatment of 50%NPK + Biost could increase crop height (47.8%) than control and same with treatment of 100%NPK. Treatment of 50%NPK + Ponti increase dry weight root (59%) than control and same with treatment of 100%NPK.The results of field research showed that bio-organic fertilizer Fertismart could increase wet weight upper crop, crop height (42.8%) and number of leaves (39.5%) than control, and same with 100%NPK. It means that bio-organic fertilizer could substitute about 50% inorganic necessity on sweet sorghum.Keywords: bio-organic fertilizer, Azotobacter, Azospirillum, phosphate solubilizing microbes.